Visuospatial working memory mediates inhibitory and facilitatory guidance in preview search - Barrett, Doug J.K.; Shimozaki, Steven S.; Jensen, Silke; Zobay, Oliver (American Psychological Association, 2016)
Visual search is faster and more accurate when a subset of distractors is presented before the display containing the target. This “preview benefit” has been attributed to separate inhibitory and facilitatory guidance mechanisms during search. In the preview task the temporal cues thought to elicit inhibition and facilitation provide complementary sources of information about the likely location of the target. In this study, we use a Bayesian Observer model to compare sensitivity when the temporal cues eliciting inhibition and facilitation produce complementary, and competing, sources of information. Observers searched for T-shaped targets among L-shaped distractors in two standard and two preview conditions. In the standard conditions, all the objects in the display appeared at the same time. In the preview conditions, the initial subset of distractors either stayed on the screen or disappeared before the onset of the search display, which contained the target when present. In the latter, the synchronous onset of old and new objects negates the predictive utility of stimulus-driven capture during search. The results indicate observers combine memory-driven inhibition and sensory-driven capture to reduce spatial uncertainty about the target’s likely location during search. In the absence of spatially predictive onsets, memory-driven inhibition at old locations persists despite irrelevant sensory change at previewed locations. This result is consistent with a bias towards unattended objects during search via the active suppression of irrelevant capture at previously attended locations.